Introduction to the research - Oikonomopoulou, Faidra (A+BE | Architecture and the Built Environment, 2019)
Innovations in glass technologies and engineering over the last decades have altered the way we perceive glass. Combining transparency, durability and a compressive strength exceeding that of concrete and even structural steel, glass has evolved in the engineering world from a brittle, fragile material to a reliable structural component with high compressive load-carrying capacity. At present, the structural applications of glass in architecture are constantly increasing, yet with a considerable geometrical limitation: although glass’s fabrication boundaries have been continuously stretching so far, glass structures are still dominated by the limited shapes which can be generated by the combination of the virtually 2-dimensional, planar elements produced by the float industry. Whereas glass panels in float production can stretch more than 20 m in length, the width is restricted to 3.21 or 4.5 m and the maximum commercial thickness is only 25 mm (Lyons 2010; Schittich et al. 2007; Patterson 2011). Cast glass can overcome the design limitations imposed by the 2-dimensional nature of float glass. By pouring molten glass into moulds, solid 3-dimensional glass components of almost any shape and cross-section can be obtained1. Such objects can be shaped to form repetitive units for free-form full-glass structures that do not buckle due to their slender proportions, thus taking full advantage of the high compressive strength of glass; a solution little explored so far. Discouraging factors such as the meticulous and time-consuming annealing process required, the to-date non-standardized production, and the corresponding high manufacturing costs, have limited cast glass to only a handful of realized architectural applications. Consequently, there is a lack of engineering data and a general unawareness of the potential and risks of building with cast glass as a structural material. The loadbearing function of cast glass in architecture remains an unmapped field. Scope of this research is to explore the structural potential and limitations of solid cast glass components and introduce cast glass as a promising construction material in architecture, indicating both the potential and limitations of this alternative production process for glass in buildings. To achieve this, the research focuses on the development and experimental validation of two new design concepts for selfsupporting envelopes made almost entirely of cast glass components: adhesively bonded and interlocking cast glass components.